Public libraries in the social inclusion of forced migrants in the Lisbon Metropolitan Area - Serra, Sofia; Revez, Jorge (Advanced Notes in Information Science, 2023)
The social inclusion of forced migrants includes responding to their information needs. This investigation seeks to analyze public librarians' perceptions of the role of public libraries in such process. The research framework is the constructivist paradigm and uses the case study method to, through the semi-directive interview technique, investigate sixteen municipal public libraries in the Lisbon Metropolitan Area. The results highlight that forced migrants are not identified users of these libraries. However, public librarians equate them to economic migrants in informational needs and behaviors, highlighting the importance of free internet access, the resources in foreign languages, the Portuguese language courses, and the help to interact with online platforms. As shortcomings, there are few Portuguese courses for foreigners, limited practice in job search, housing and inclusive collaboration with schools, and limitations in terms of space and human and financial resources. These difficulties can be overcome with the motivation to fulfil the public library's inclusive social mission, its universal accessibility and informal environment, and the promotions of cohesion and social capital. While the mission of libraries fits the purpose of forced migrants’ inclusion, the education and training of librarians could be improved. It is recommended that the public libraries increase their proactivity and collaboration with existing inclusion networks. In conclusion, this research aims to raise awareness of the urgency of developing a strategic plan for Portuguese public libraries for the social inclusion of forced migrants, and to promote its institutional and social legitimacy.